Comportamento da helicônia golden torch (Helicônia psittacorum x Helicônia spathocircinada) submetida a fontes e doses de silício - Santos, José Manzil dos (2006)
Silício (Si) is an element that interest is appearing very interesting between technician and formers by their benefits numberless that bring to culture. The work in studyng has had the objective to value conduct of Helicônia Golden Torch (Heliconia psittacorum x Helicônia spathocircinda) in Silício doses and sour function by soil in vase. The trail has benn conducting at nursery with shady 50% in an area of Federal School, in the municipality of Satuba-AL. The experimental delineation factorial schem (3 sources of Silício and 4 doses of Si) with four repetitions; in 48 experimental units, totally. The work was been conducting of form that definite treatments have had these results. T1) 0 mg dm-3 from (Si) as cement; T2) 250 mg dm-3 from (Si) as cement; T3 500 mg dm-3 from (Si) as cement; T4) 750 mg dm-3 from (Si) as cement; T5) 0 mg dm-3 from (Si) as Silicato of Cálcio; T6) 250 mg dm-3 from (Si) as Silicato of Cálcio; T7) 500 mg dm-3 from (Si) as Silicato of Cálcio; T8) 750 mg dm-3 of itself as Silicato of Cálcio; T9) 0 mg dm-3 from (Si as Silicato of Sódio; T10) 250 mg dm-3 from (Si) as Silicato of Sódio; T11) 500 mg dm-3 from (Si) as Silicato of Sódio: T12) 750 mg dm-3 from (Si) as Silicato of Sódio. Founded in obtained results by analysis of average and variation, I concluded that in general lines the Silicato of Sódio, promoted better results of length of bractea; of length of floral stem, with the dose of 500 mg dm-3 of Silício show better results. The quantity of Silício in the leaf rose with doses of elements and the best results I obtained with Silicato of Cálcio the burning of the bráctea was less shown we applicate the Silicato of Cálcio in dose of 500 mg dm-3 of Silício.